2004
DOI: 10.1016/j.jacc.2004.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and caffeine have a synergistic detrimental effect on aortic stiffness and wave reflections

Abstract: The present study shows, for the first time, that when smoking and caffeine intake are combined, they interact and exert a synergistic, unfavorable effect on aortic stiffness and wave reflections on both an acute and chronic basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
73
1
26

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 36 publications
10
73
1
26
Order By: Relevance
“…This study extends the findings of our previous studies that showed that caffeine increases acutely aortic stiffness and wave reflections both in normotensive and hypertensive patients (Vlachopoulos et al, 2001(Vlachopoulos et al, , 2003a(Vlachopoulos et al, , b, 2004a, and that chronic coffee consumption is associated with increased aortic stiffness and wave reflections in healthy normotensive subjects without cardiovascular risk factors, except from smoking (Vlachopoulos et al, 2004a(Vlachopoulos et al, , 2005a. Interestingly, the findings of the present study are not a direct extrapolation of the findings in normotensive subjects, because, contrary to those, only wave reflections are affected, indicating a different behaviour of large and small arteries in hypertension.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study extends the findings of our previous studies that showed that caffeine increases acutely aortic stiffness and wave reflections both in normotensive and hypertensive patients (Vlachopoulos et al, 2001(Vlachopoulos et al, , 2003a(Vlachopoulos et al, , b, 2004a, and that chronic coffee consumption is associated with increased aortic stiffness and wave reflections in healthy normotensive subjects without cardiovascular risk factors, except from smoking (Vlachopoulos et al, 2004a(Vlachopoulos et al, , 2005a. Interestingly, the findings of the present study are not a direct extrapolation of the findings in normotensive subjects, because, contrary to those, only wave reflections are affected, indicating a different behaviour of large and small arteries in hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…The chronic effect of coffee consumption on arterial elastic properties is less well studied. As we have previously shown, coffee consumption has a chronic detrimental effect on aortic stiffness and wave reflections in normotensive subjects (Vlachopoulos et al, 2004a(Vlachopoulos et al, , 2005a. However, the association between chronic coffee consumption, and arterial stiffness and wave reflections in hypertensives, that is, a population with already impaired elastic properties, has not been examined yet.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Caffeine levels peak 30-120 min after oral intake and caffeine's half-life is 3-6 h. Caffeine tolerance diminishes the acute effect of caffeine on BP, and hypertensive individuals are more susceptible to BP changes with caffeine administration and/or intake. 10 Various components, including cigarette smoking and caffeine, are being increasingly investigated for the possible impact on arterial stiffness (AS) and wave reflection and on cardiovascular risk. 11,12 Caffeine consumption is a risk factor for heart failure, but its effects remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, systolic BP (SBP) and, pulse pressure are amplified from the ascending aorta to the brachial artery where BP is traditionally measured. The magnitude of pressure amplification may vary and is influenced by several demographic variables including age, gender and height, 3 as well as clinical and physiological factors such as hypercholesterolemia, 4 recreational stimulants, 5 vasoactive medications, 6 mean arterial pressure, 3 heart rate, 7 exercise 8 and posture. 9 Thus, brachial cuff measures of BP may not reliably estimate central SBP and pulse pressure.…”
Section: Introductionmentioning
confidence: 99%